Terapi Komplementer Akupressur dalam Mengatasi Morning Sickness pada Ibu Hamil Trimester I - Nurbaiti, Nurbaiti; Perwitasari, Tuhu; Nurita, Suci Rahmani (Universitas Baiturrahim, 2024)
Nauseous vomiting is caused by Changes in the endocrine system in the body that occur during pregnancy are due to high fluctuations in HCG levels (human chrinic gonadotropin) Although nausea and vomiting is a physiological thing, if proper treatment is not carried out, it will turn into pathology where it can affect the health of the mother and fetus, such as malnutrition so that adequate nutrition can be obtained which can cause low birth weight or prematurity. This activity aims to increase the knowledge and understanding of pregnant women and mothers who can do it independently at home in copingmorning sickness. This activity is carried out on the month October 2022 to January 2023 took place at PMB Rosmala Aini Jambi City, which was attended by 20 pregnant women, with lecture, discussion and question and answer methods, the media used was in the form of leaflets, meeting time+ 90 minutes. At the implementation stage, before and after giving the material, an evaluation of the knowledge of pregnant women throughpretest andposttestby using a questionnaire. the result of this activity is an increase in the knowledge of pregnant women with a value before education for mothers with less knowledge of 90% and after education the mother's knowledge becomes good to 85% based on this, it can be concluded that mother's knowledge increases and it is hoped that mothers can do it independently.